SPECTRAL EVALUATION AND ANTIMICROBIAL ACTIVITY OF SYNTHESIZED 4H-1,4-BENZOTHIAZINES - GOYAL, ARUN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: 4H-1,4-Benzothiazines constitute an important class of heterocycles containing 1,4-thiazine ring fused to benzene ring. They are extensively used as tranquilizer, antispasmodic, central nervous system depressant, antiulcer, antibacterial, antifungal, antioxidant, anticancer agents, fungicides, etc. Therefore, these observations prompted us to synthesize substituted 4H-1,4-benzothiazines and investigate their antimicrobial activity against selected bacterial and fungal strains. Methods: In the present research work, 2-Amino-3,5,6-trichlorobenzenethiol condensed with β-diketones/β-ketoesters in the presence of dimethyl sulfoxide followed by oxidative cyclisation leading to the formation of 4H-1,4-benzothiazines. The spectral investigation confirmed the synthesis of these bioactive compounds. All synthesized compounds were screened for their antimicrobial activity (antibacterial and antifungal) using agar well diffusion method. Results: The minimum inhibitory concentration values of synthesized compounds gave excellent results against bacterial as well as fungal strains (Escherichia coli [Gram negative] MTCC 2939, 58–158 μg/mL, Bacillus subtilis [Gram positive] MTCC 441, 41–124 μg/mL, Streptomyces griseus [Gram negative] MTCC 1998, 85–128 μg/mL, Fusarium oxysporum MTCC 1755, 142–151 μg/mL, Aspergillus niger MTCC 281, 59–78 μg/mL, and Rhizopus stolonifer MTCC 2591, 85–118 μg/mL). Conclusion: Synthesized substituted benzothiazines have potential to be used as a new class of antibacterial and antifungal drugs. Further biomedical research is required to make 4H-1,4-benzothiazines related compounds as potential antibacterial and antifungal drugs.